Oxford Handbooks Online 2015
DOI: 10.1093/oxfordhb/9780199783267.013.10
|View full text |Cite
|
Sign up to set email alerts
|

Moving Toward Universal Definitions and Assessment of Relational Problems

Abstract: In this chapter, we review the utility of universal definitions and the assessment of family problems and family violence from a public health perspective. First, we document the clinical implications and public health costs of intimate partner violence, child abuse, intimate partner relationship distress, and parent–child relational problems. Second, the current status of these problems in major diagnostic systems and recommendations for improvements in universal assessment are detailed. Third, brief measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Vignettes depicted patients presenting with relatively mild RPM, which included instances of IPV (i.e., physical and psychological partner violence) that met minimum definitional requirements for an RPM, as well as relationship distress with a spouse or intimate partner. Relationship distress is not a form of IPV; it was included because it is an important risk factor for IPV ( Stith et al, 2008 ) and is associated with negative mental health outcomes (e.g., depression, anxiety, and alcohol use disorder; Foran et al, 2015 ; Whisman, 2007 ). Less prevalent forms of IPV (e.g., sexual partner violence) were not included due to concerns about survey length.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vignettes depicted patients presenting with relatively mild RPM, which included instances of IPV (i.e., physical and psychological partner violence) that met minimum definitional requirements for an RPM, as well as relationship distress with a spouse or intimate partner. Relationship distress is not a form of IPV; it was included because it is an important risk factor for IPV ( Stith et al, 2008 ) and is associated with negative mental health outcomes (e.g., depression, anxiety, and alcohol use disorder; Foran et al, 2015 ; Whisman, 2007 ). Less prevalent forms of IPV (e.g., sexual partner violence) were not included due to concerns about survey length.…”
Section: Discussionmentioning
confidence: 99%
“…Intimate partner violence (IPV) is defined as any behavior within a relationship that causes—or has reasonable potential to cause—physical, sexual, or psychological harm to a partner ( Foran et al, 2015 ; WHO, 2012). Globally, it is estimated that 35% of ever-partnered women have experienced lifetime IPV (WHO, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beach et al ( 2016) described DSM-IV' s and ICD-10' s inclusion of criteria-free codes for relational problems and the process of expanding criteria for DSM-5 and the proposed ICD-11. As noted in Beach et al (2016) and Foran et al (2016), whereas DSM' s exclusive focus is on mental health diagnoses, the ICD encompasses all medical problems (including mental health), given its mandate for worldwide clinical, health system, and public health usefulness. Thus, the ICD necessitates a more holistic approach as well as a more explicit recognition of the variety of contexts and cultures in which the ICD is used.…”
Section: Relational Problems In the Dsm-5 And Proposed Icd-11mentioning
confidence: 99%
“…With about the same prevalence for lifetime experience of both psychological and physical IPV. The public health burden of these problems and their sequelae are tremendous (Foran et al, 2013). Studies of the antecedents of physical IPV have found communication and problem-solving disputes (and the accompanying emotionality in these disputes) to be the most common proximal precipitants (Langhinrichsen-Rohling et al, 2012; O’Leary & Slep, 2006).…”
mentioning
confidence: 99%